1997
DOI: 10.2527/1997.75113082x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and transitional regulation of gluconeogenesis and glyconeogenesis by insulin and glucagon in neonatal calf hepatocytes.

Abstract: Milk-fed calves were used as a source of hepatocytes to establish monlayers to test the effects of chronic (41 h) incubation with no hormone, 100 nM insulin, or 100 nM glucagon on gluconeogenesis (glucose retained as glycogen plus glucose released into the medium) from 2.5 mM [2-(14)C]propionate and 2.0 mM [U-14C]lactate (1.0 mM lactate plus 1.0 mM pyruvate) during a subsequent 3-h (acute) incubation. Media for acute incubations contained no hormone, 0 or 10 nM insulin, or 0, 1, 10, or 100 mM glucagon. Chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Therefore, gluconeogenic enzymes were differently affected by metabolic and endocrine changes and supported the findings in dairy cows (Hammon et al, 2009) that changes of gluconeogenic enzymes may be differently regulated. Furthermore, the abovementioned impairment of endocrine regulation on eGP in neonatal calves is probably reflected by the low endocrine response on gluconeogenic enzymes (Donkin et al, 1997;Scheuer et al, 2006). Changes in PEPCK activities indicate that this enzyme likely was a rate-limiting enzyme, but other gluconeogenic enzyme activities measured herein were more or less unaffected by changes in ontogenic state.…”
Section: Ontogenic Effects On Hepatic Changes Of Glucose and Fat Metamentioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, gluconeogenic enzymes were differently affected by metabolic and endocrine changes and supported the findings in dairy cows (Hammon et al, 2009) that changes of gluconeogenic enzymes may be differently regulated. Furthermore, the abovementioned impairment of endocrine regulation on eGP in neonatal calves is probably reflected by the low endocrine response on gluconeogenic enzymes (Donkin et al, 1997;Scheuer et al, 2006). Changes in PEPCK activities indicate that this enzyme likely was a rate-limiting enzyme, but other gluconeogenic enzyme activities measured herein were more or less unaffected by changes in ontogenic state.…”
Section: Ontogenic Effects On Hepatic Changes Of Glucose and Fat Metamentioning
confidence: 74%
“…Plasma lactate is decreased more after delivery by section in term-born calves than in preterm calves (Sangild et al, 2000), which confirms our observations. Elevated plasma lactate concentrations may indicate less oxygen consumption or less lactate utilization; for example, as substrate for GNG or energy fuel, in PT calves, because lactate is an important substrate for GNG in neonates (Donkin et al, 1997). In addition, lactate serves as a substrate for the TCA cycle (Voet and Voet, 1994).…”
Section: Ontogenic Changes Of Hormones and Additional Metabolitesmentioning
confidence: 99%
“…As previously mentioned glycogen mobilization is provoked mainly by catecholamine increase supported by a decreased insulin/ glucagon molar ratio. There is a lot of evidence that proves that glucagon by itself is ineffective in triggering neonatal liver glycogenolisys [44,45]. The partial resistance to glucagon stimulation by neonatal (and also fetal) hepatocytes could be due to (a) the lower number of high affi nity receptors, or (b) an impaired coupling of the receptor with adenilate cyclase [46].…”
Section: Insulin and Glucagonmentioning
confidence: 99%
“…Circulating insulin and glucagon concentrations are linked to synthesis of glucose, which is a major source of energy in ruminants, and the energy status can be estimated from the insulin/glucagon concentration ratio [8]. The insulin/glucagon concentration ratio is responsive to physiological condition such as growth, lactation, diet, and feeding patterns [3]. The cattle with growth retardation in this study showed lower insulin and normal glucagon concentrations immediately before injections, resulting in lower insulin/ glucagon concentration ratios than in the control.…”
mentioning
confidence: 99%